Study on pH and somatic cell count in milk of sub-clinical mastitic cows in association with udder and teat shape (Indian Journal of Animal Production and Management, 2018)
Present experiment was conducted to study the pH and somatic cell count (SCC) in milk of mastitic cows  in association with udder and teat shape. Total 150 lactating Gir cows of different parities and at different  stages of lactation from different location of Anand district of Gujarat were randomly selected. Dairy farms  were visited in sequential manner and data were carefully collected personally. Cows were fed available  green and dry roughages, compounded concentrate mixture and handful of mineral mixture. Clean  wholesome drinking water was provided ad libitum to all the cows. Freshly drawn evening milk samples  (approximately 10 ml) of all four quarters of all the150 experimental Gir cows were collected and subjected  to pH estimation and somatic cell count (SCC). pH reading was recorded by digital pH meter after calibration  of the pH probe. The pH level more than 6.8 indicated the incidence of subclinical mastitis. Laboratory test  for estimation of SCC was done using FossomaticTM Minor cell counter. Samples with more than 5,00,000  SCC/ml of milk were considered as subclinical mastitis positive. There was elevation in milk pH value in  subclinical mastitis (SCM) cows (7.1 ± 0.01) as compared to the healthy cows (6.65 ± 0.01). Among SCM  cows with different shape of udder, cows with goaty udder had the highest milk pH values whereas cows  with round shape udder had minimum pH value. Similarly, SCM cows with cylindrical shape teat had  higher milk pH than the SCM cows with funnel, bottle and pear shape teats. However, differences in milk  pH value between right and left and fore and hind quarters of SCM cows were not appreciable. There was  elevation in milk SCC in SCM cows (1802.48 ± 82.54 × 103) as compared to the healthy cows (122.46  ± 6.26 × 103). The SCC of milk samples collected from different udder and teat shape and right and left  quarter and fore and rear quarters showed similar pattern i.e., higher SCC in SCM cows as compared to  healthy cows. The study indicated that selection of Gir cows for trough and round udder may reduce the  milk SCC and the incidences of subclinical mastitis.
Keywords: Cow; pH; Somatic cell count; Subclinical mastitis; Teat; Udder